Omics In Soil Science - Nannipieri, Paolo; Pietramellara, Giacomo; Renella, Giancarlo (Caister Academic Press, 2014)
Soil is a unique biological system with an abundant microflora and a very high microbial diversity capable of performing multiple key ecosystem functions. The detection of genes in soil has improved the knowledge of unculturable microorganisms and led to a greater understanding of potential soil metabolic pathways. Further advances in understanding soil functionality are being realized by harnessing omics technologies, such as metagenomics, metatranscriptomics, proteomics, and volatilomics. The next challenge of systems biology and functional genomics is to integrate the information from omic.